Survival Rate Against Fracture of Endodontically Treated Premolars Restored with Crowns and Resin Composites: A Retrospective Study - Enas Khamakhim,; Farida Alsayeh, (AlQalam Journal of Medical and Applied Sciences, 2024)
The purpose of this study was to assess the survival rate of endodontically treated premolars that were restored with resin composites or crowns. Additionally, possible risk factors were identified through the use of a retrospective cohort design. Based on inclusion and exclusion criteria, dental records of premolar ETT with crowns or composite restorations (recall period, 2018–2023) were gathered. Both the existence of the fracture and any potential prognostic variables were noted. Analysis using statistical methods was done at a significance level of P <0.05. The Chi square test was used for all comparisons, and frequency and percentages were used to depict the qualitative data. There was a significant difference in the survival rates against breakage between teeth replaced with crowns (95.1%) and resin composites (62.1%) (P<0.05). The results showed that there was a significant difference between them in terms of sex, age, opposing dentition, crestal bone level, and fracture incidence. Regarding premolars that have undergone endodontic treatment, crown restorations outperformed resin composites in terms of survival rate. Premolars receiving endodontic therapy and having crestal bone loss up to the middle third of the root were shown to be at an increased risk of fracture. هذه الدراسة عبارة عن تقييم مقاومة الكسر للضواحك المعالجة لبياً والتي تم ترميمها باستخدام حشوات الراتنج أو التيجان. بالإضافة إلى ذلك، تم تحديد عوامل الخطر المحتملة بأثر رجعي. الطرق: بناءً على معايير الاشتمال والاستبعاد، تم جمع سجلات لأسنان الضواحك المعالجة لبيا بعد ان ثم تركيب التيجان أو الترميم بإستخدام حشوات الراتنج (فترة الاستدعاء، 2018-2023). ولوحظ وجود الكسر وأي متغيرات محتملة. تم إجراء التحليل باستخدام الأساليب الإحصائية عند مستوى دلالة P <0.05. تم استخدام اختبار مربع كاي لجميع المقارنات، وتم استخدام التكرار والنسب المئوية لتصوير البيانات النوعية. النتائج: كان هناك اختلاف كبير في معدلات مقاومة الكسر بين الأسنان المغلفة بالتيجان (95.1%) على الأسنان المعالجة بواسطة الحشوات الراتنجية (62.1%) (P<0.05). أظهرت النتائج وجود اختلاف كبير بينهما من حيث الجنس والعمر والأسنان المقابلة ومستوى العظم وحدوث الكسور. الاستنتاجات: فيما يتعلق بالضواحك التي خضعت للعلاج اللبّيّ، فقد تفوقت ترميمات التاج على المركبات الراتنجية من حيث معدل البقاء. تبين أن الضواحك التي تتلقى علاجًا لبيًا وتعاني من فقدان ثلث العظم تكون أكثر عرضة لخطر الكسر.